2012
DOI: 10.1016/j.kjms.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers associated with nonepithelial ovarian cancer in formalin‐fixed, paraffin‐embedded specimens by genome wide expression profiling

Abstract: Nonepithelial ovarian cancer (NEOC) is a rare cancer that is often misdiagnosed as other malignant tumors. Research on this cancer using fresh tissues is nearly impossible because of its limited number of samples within a limited time provided. The study is to identify potential genes and their molecular pathways related to NEOC using formalin-fixed paraffin embedded samples. Total RNA was extracted from eight archived NEOCs and seven normal ovaries. The RNA samples with RNA integrity number >2.0, purity >1.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These events occur as a response to the tumour microenvironment, immunological changes and their proliferation [ 20 ]. The subunits involved in the translational machinery of OC in tumour tissue or cell lines has been reported for eIF6 [ 13 , 14 , 21 , 22 ], eIF5A [ 23 26 ], eIF5B [ 27 ], eEF1 [ 28 30 ] and eIF2α [ 31 36 ]. No reports were found to have directly assessed eIF2G (or synonym eIF2S3) for OC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These events occur as a response to the tumour microenvironment, immunological changes and their proliferation [ 20 ]. The subunits involved in the translational machinery of OC in tumour tissue or cell lines has been reported for eIF6 [ 13 , 14 , 21 , 22 ], eIF5A [ 23 26 ], eIF5B [ 27 ], eEF1 [ 28 30 ] and eIF2α [ 31 36 ]. No reports were found to have directly assessed eIF2G (or synonym eIF2S3) for OC.…”
Section: Discussionmentioning
confidence: 99%
“…For eEF1A, interestingly, a gene expression study on non-epithelial ovarian cancer (granulosa cell tumor, mixed germ cell tumor, yolk sac tumour, immature teratoma, malignant mature teratoma, dysgerminoma, thecoma and juvenile granulosa cell tumor) was performed to compare expression with normal ovarian tissue. It was shown that cytoplasmic expression of eEF1A was increased in non-epithelial ovarian cancer [ 28 ]. Furthermore, it was shown that eEF1A2 overexpression was present in 75% of clear cell carcinomas, which is higher than in other histological subtypes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its rare incidence of this subtype of ovarian cancer, we have performed microarray assay on the formalin-fixed paraffin embedded tissues (63). About 804 differentially expressed genes with at least 2-fold change (P<0.005) (63).…”
Section: Gene Expression Profiling In Ovarian Cancermentioning
confidence: 99%